Criminal Case of Unlicensed Mining (PETI) of Bauxite Ore by the Criminal Investigation Unit of Tanjung Pinang Police - Ismaidar Ismaidar; Tamulina Br. Sembiring; Muhammad Aldin (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2025)
Tanjung Pinang City, with its natural resource potential in the form of bauxite ore, has experienced problems related to illegal mining activities (PETI) involving CV. Tri Karya Abadi. This case began with a report by PT Kemayan Bintan regarding theft and land grabbing in 2009. Investigations showed that CV. Tri Karya Abadi, despite having a limited permit, carried out exploitation outside the permitted area, utilizing heavy equipment and manipulative methods to obtain maximum profit. These activities resulted in the export of large amounts of bauxite to foreign countries. The investigation by the Criminal Investigation Unit of the Tanjung Pinang Police faced procedural obstacles, but succeeded in determining the main suspect and documenting the violations through the Investigation Report (BAP). In its resolution, this case dragged various parties with the application of sanctions based on Law No. 4 of 2009. An important lesson from this case is the need for synergy between the community, the police, and related agencies to prevent and take firm action against illegal mining activities. Consistent law enforcement with a multi-door system approach is key to protecting the environment and ensuring legal compliance.